2012
DOI: 10.1021/ef3007992
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Gasification of Nannochloropsis sp. with Ru/C

Abstract: We determined the effects of different process variables on the gasification of Nannochloropsis sp., a marine microalga, in water with a Ru/C catalyst at 410 °C. About 45% gasification efficiency was achieved at 75 min with a catalyst loading (mass of Ru/C catalyst/mass of dry algal biomass) of 1 g/g, a water density of 0.096 g/cm 3 , and a 4.3 wt % loading of algae. Longer reaction times, higher catalyst loadings and water densities, and lower algae loadings provided higher gas yields. The level of catalyst l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Moreover, Osada and co-workers [29][30] have demonstrated that ruthenium-based catalysts are stable in hydrothermal conditions after regeneration but may require slightly longer residence time to perform at the same level as the fresh catalyst. In addition, other authors [31][32] have reported that sulphur-poisoning was a major cause of deactivation of ruthenium catalyst; hence this was not expected in this work as the feedstock used contained no sulphur. The SEM micrographs in Figure 7 present the details of the surfaces of the fresh, used non-calcined and used calcined 20 wt% RuO2/ -Al2O3 catalyst.…”
Section: Analysis Of Used Catalystsmentioning
confidence: 76%
“…Moreover, Osada and co-workers [29][30] have demonstrated that ruthenium-based catalysts are stable in hydrothermal conditions after regeneration but may require slightly longer residence time to perform at the same level as the fresh catalyst. In addition, other authors [31][32] have reported that sulphur-poisoning was a major cause of deactivation of ruthenium catalyst; hence this was not expected in this work as the feedstock used contained no sulphur. The SEM micrographs in Figure 7 present the details of the surfaces of the fresh, used non-calcined and used calcined 20 wt% RuO2/ -Al2O3 catalyst.…”
Section: Analysis Of Used Catalystsmentioning
confidence: 76%
“…The reactors had an internal volume of 4 cm 3 . The reactor had a Swagelok cap on one end and a HiP high-pressure valve assembly on the other, which were described in greater detail in our previous reports [14,15].…”
Section: Methodsmentioning
confidence: 99%
“…Previous work [15] indicates that Ru/C is easily poisoned by sulfur, and suffered from rapid activity decrease after reuse. sulfur linkage could be hydrolyzed to hydrogen sulfide during hydrolytic degradation of alkaline lignin [16].…”
Section: Catalyst Durabilitymentioning
confidence: 99%
“…As the increase of biomass loading, the efficiency of gasification and gaseous yields decrease dramatically due to the lower steam reforming reactions [12,13]. It is found that as the concentration of glucose increases from 10 to 24%, the hydrogen yield decreases from 8.9 to 2 mol·kg − 1 and the CO yield decreases from 7.9 to 5.9 mol·kg −1 .…”
Section: Effect Of Biomass Loadingmentioning
confidence: 99%
“…water provides a potential way to convert biomass to fuel-rich gas containing H 2 and/or CH 4 [12,13]. Commercial SCWG facility can be found for treatment of surplus active sludge for gaseous fuels in Japan, but Matsumura's evaluation indicates that SCWG requires a significant amount of energy to pre-heat and maintain a desired high temperature for the reactions [14].…”
Section: Introductionmentioning
confidence: 99%